Financial intermediation and fire sales with liquidity risk pricing - Yuteng Cheng; Roberto Robatto (Bank of Canada, 2024)
We provide a theory of fire sales in which potential buyers are subject to liquidity shocks and frictions that limit their ability to resell assets. The model predictions align with some stylized facts about the large sales of corporate bonds and Treasury securities during the COVID-19 economic crisis. The equilibrium is constrained efficient under weak conditions that apply if one interprets the key agents in the model as money market funds or mutual funds. Thus, as viewed through the lens of the model, the liquidity requirements proposed by the U. S. Securities and Exchange Commission for these intermediaries could hurt the economy.
Keywords: G12; G23; G28; 330; Asset pricing; Financial markets; Financial system regulation and policies